Growth and Yield Response of Peanut (Arachis hypogaea L.) to Cow Manure Dosage and Phosphorus Fertilizer on Ultisol - Silitonga, Listati; Turmudi, Edhi; Widodo, Widodo (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
ABSTRACTPeanut plant production has decreased almost every year, caused by several factors such as cultivation techniques, diseases, varieties, competition with other commodities and the increasingly narrow land area. One effort to improve the yield of peanuts by optimizing ultisol land for cultivation of plants. Ultisol soil is one of acid soils, high Al content, low organic matter content, and low cation exchange capacity. Provision of fertilizer is one effort made to maximize the use of ultisol land. This study aims to determine the optimal dose of cow manure and phosphorus fertilizer for peanut plants and to determine the dose of cow manure and the appropriate dose of phosphorus fertilizer for peanut plant. The design used in this experiment was Randomized Complete Block Design (RCBD) with two factors arranged factorially. The first factor was dosage of cow manure consisting of 4 treatment levels i.e. 0 ton ha-1, 10 ton ha-1, 20 ton ha-1 and 30 ton ha-1. The second factor is phosphorus fertilizer (SP-36) consisting of 3 levels i.e. 0 kg ha-1, 100 kg ha-1 and 200 kg ha-1. From these two factors, there were 12 treatment combinations each treatment was repeated 3 times, so that 36 experiments were obtained. The results showed that the dosage of cow manure did not significantly affect the growth and yield of peanut plants. The dosage of phosphorus fertilizer did not significantly affect all variables of observation except on seed weight. The combination of dosage of cow manure and phosphorus fertilizer has no significant effect on the growth and yield of peanut plant. Keywords: Peanut, Cow Manure, Phosphorus and Ultisol